Management of Extensive Forearm Injury – A Case Report (Indian Journal of Case Reports, 2021)
Upper limb injuries are a common occurrence in countries like India. Here, we report the case of a 52-year-old gentleman with severe flexor tendons and neurovascular injury which was managed on an emergency basis. Clinical examination revealed multiple flexor tendons and ulnar nerve and artery injuries. Intraoperatively, the tendons were repaired with the flexor carpi radialis requiring tendon transfer. Ulnar artery cut ends were anastomosed and the ulnar nerve was repaired. The patient was taught some passive exercises and given physiotherapy. On follow-up, the patient showed satisfactory recovery, highlighting the importance of early exploration and repair.